2021
DOI: 10.1007/s11145-021-10126-9
|View full text |Cite
|
Sign up to set email alerts
|

Reading comprehension on word- and sentence-level can be predicted by orthographic knowledge for German children with poor reading proficiency

Abstract: Previous studies mostly examined the role of orthographic knowledge in basic reading processing (i.e., word-reading), however, regarding higher reading processing (i.e., sentence- and text-comprehension), mixed results were reported. In addition, previous research in transparent languages, such as German, focused mostly on typically skilled readers. The aim of this study was to examine the role of orthographic knowledge in basic reading processing (word-reading) as well as in higher reading processing (sentenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Other authors have also argued for training sight words in reading because a very important part of teaching reading is teaching sight words and irregular words as they contribute to text comprehension (Sullivan et al, 2013). Studies showed a positive relationship between word knowledge and word pattern knowledge on basic word reading (in poor German readers) (Rothe et al, 2015;Zarić et al, 2020;Zarić & Nagler, 2021) and on sentence-level reading (Zarić & Nagler, 2021). These results underline the necessity of training orthographic knowledge to enhance reading proficiency.…”
Section: The Signification Of Word Recognition Skills For Text Comprehensionmentioning
confidence: 89%
“…Other authors have also argued for training sight words in reading because a very important part of teaching reading is teaching sight words and irregular words as they contribute to text comprehension (Sullivan et al, 2013). Studies showed a positive relationship between word knowledge and word pattern knowledge on basic word reading (in poor German readers) (Rothe et al, 2015;Zarić et al, 2020;Zarić & Nagler, 2021) and on sentence-level reading (Zarić & Nagler, 2021). These results underline the necessity of training orthographic knowledge to enhance reading proficiency.…”
Section: The Signification Of Word Recognition Skills For Text Comprehensionmentioning
confidence: 89%
“…This is an example of lean production, a manufacturing method that ______ 9 to reduce waste. When you ______ 10 waste or anything else that costs unnecessary money, you will be ______ 11 the profits of your company. Some of ______ 12 major car companies out there today are still ______ 13 operations because they created a lean production method ______ 14 works for them.…”
Section: Figure 1 Sample Of Listening Exercisementioning
confidence: 99%
“…It is noted that students at technical universities have a positive perception of mobile assistance in language education, therefore they effectively use mobile devices to improve their language skills. Zarić and Nagler [10] stated that students should be able to search for specific necessary information in a text, as well as be able to deduce the meaning of unknown words from the context. They should also be motivated to feel the need to read and look for new information and then succeed in the final testing.…”
Section: Introductionmentioning
confidence: 99%
“…Fluency and correct pronunciation are not sufficient but understanding the written text is the key in learning a language. Efficient reading leads to successful learning in an educational setting (Treiman, 2018;Zarić & Nagler, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%